Knowledge, attitude and practices of biomedical waste management among interns of SDMCMSH, Dharwad - Priya, Prachi; Dixit, Umesh R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Total biomedical waste produced globally is 484 tonnes per day (TPD). 447 TPD is treated and 37 TPD is untreated. Hospital waste causes contamination of environment and leads to serious health consequences in healthcare workers and general public due to poor handling as a result of inadequate and improper treatment knowledge. Every health care professional should have a proper knowledge and capacity to guide others regards proper management of biomedical waste. The objective of the present study was conducted to assess the knowledge, attitude and practice of biomedical waste management among interns of SDMCMSH, Dharwad. Methods: A cross-sectional hospital based study was conducted to assess knowledge, attitude and practice of biomedical waste management among interns of SDMCMSH, Dharwad. There were 100 interns in the institute and all 100 were included in the study after obtaining informed consent. Pre-tested, semi-structured questionnaire was used to collect the data. Results: Out of 100 responses obtained, 81 were complete in all respect hence, and others were excluded from the analysis. Majority, 55.5% were females. 15% of the interns were not able to name correctly color codes of bags. Only two-third were aware about where and how bio-medical wastes are treated. In general, males gave correct answers more often compared to female interns and this was statistically significant (p<0.05). Conclusions: Though interns are aware about the seriousness of the biomedical waste to the public health, there still exists a knowledge attitude and practice gap. This needs to be identified and suitably addressed.